Research Trends in Project-Based Learning in Elementary Schools (2001-2024): Bibliometric Analysis - Purwandari, Purwandari; Huriawati, Farida; Sarry, Viola Dea Amanda; Susanti, Ita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Project-Based Learning (PjBL) is an educational method that engages students in completing projects relevant to real-life contexts, fostering critical thinking and problem-solving skills. This study aims to systematically analyze trends and developments in research related to PjBL in primary schools through a bibliometric approach, providing insights into the method's implementation in primary education. The study employs data retrieved from the Scopus database using the Publish or Perish tool, which is analyzed with VOSviewer to visualize trends in collaboration, keywords, and contributions of prominent authors. Over the past two decades (2001–2024), 173 publications have been identified, with a notable surge in research output beginning in 2017 and peaking in 2020. The analysis highlights keywords such as